Scientific documentation required during the exploration of caves and technical work carried out in tourist show caves ‒ examples from central Poland - Urban, Jan; Tyc, Andrzej; Kasza, Andrzej; Ślusarczyk, Marceli (Geotourism/Geoturystyka, 2018)
The procedure of scientifi c documentation of caves explored and/or arranged for touristic use is proposed and recommended in this paper. This procedure has been verifi ed on the basis of work done during the arrangement of the Underground Touristic Trail combining three caves in the Kadzielnia Park, city of Kielce, Świętokrzyskie (Holy Cross) Mountains, and Jaskinia Głęboka (Deep Cave) in the “Góra Zborów” nature reserve, Kraków–Częstochowa Upland. The objective of the cave documentation is the preservation of scientifi c evidence of the geological history of karst systems and the region, which are recorded in sequences of cave sediments (including their physical, petrographic and mineralogical properties, palaeontological remains and archaeological artefacts), mineralogical and isotopic composition of speleothems and specifi c features of cave morphology. These elements are often totally or partially destroyed (i.e. removed, changed in shape) during cave exploration and/or any technical work carried out in tourist caves. This makes it necessary to document thier scientifi c study, which is also required by law. The procedure of such documentation and study proposed and verifi ed in this paper include the photographic documentation of sediments and cave morphologies, sampling of sediments, as well as their basic petrographical-palaeontological analyses, which make it possible to plan exploration, technical work and further research.//Artykuł proponuje procedurę dokumentacji naukowej jaskiń, które są eksplorowane oraz przygotowywane do udostępnienia turystycznego. Procedura ta została zweryfi kowana podczas prac udostępniających Podziemną Trasę Turystyczną łączącą trzy jaskinie w parku Kadzielnia w Kielcach na terenie Gór Świętokrzyskich oraz Jaskinię Głęboką w rezerwacie przyrody „Góra Zborów” na Wyżynie Krakowsko-Częstochowskiej. Celem naukowej dokumentacji jaskiń jest zachowanie świadectw geologicznego rozwoju i ewolucji systemu krasowego oraz regionu, w którym system ten powstał. Świadectwa te zapisane są w sekwencjach osadów namuliskowych (w postaci ich cech fi zycznych, petrografi cznych oraz mineralogicznych, a także artefaktów paleontologicznych i archeologicznych), w mineralnym oraz izotopowym składzie nacieków i w morfologii jaskiniowej. Te elementy są często całkowicie lub częściowo niszczone(osady są usuwane, rzeźba ścian zmieniana) w czasie prac eksploracyjnych i/lub prac górniczo-technicznych w jaskiniach udostępnianych turystycznie. To stwarza konieczność wykonywania dokumentacji i badań naukowych, które wynikają również z przepisów prawnych. Proponowana procedura prac dokumentacyjno-badawczych obejmuje: dokumentację opisową i fotografi czną sekwencji osadów oraz rzeźby jaskini, opróbowanie osadów, a także podstawowe analizy petrografi czne i paleontologiczne, które umożliwiają właściwe planowanie oraz prowadzenie dalszych prac eksploracyjnych i górniczo-technicznych a także dalszych badań.